Tantangan Komunikasi Generasi Z dalam Perkembangan Digital di Era Teknologi 5.0 - Juliyah Juliyah; Romawinsa Siringoringo; Siti Rohma; April Laksana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The development of technology is very rapid and has undergone a significant transformation, especially with the emergence of technology 5.0. In this development, Generation Z is experiencing communication challenges in the development of the 5.0 technology which is increasing. The purpose of this research is to analyze the Communication Challenges of 5.0 in the Digital Age and Understand Generation Z in communicating with the rapid advancement of 5.0 technology. This research is a literature study. Data collection uses documentation from Google School. The data analysis used is the Systematic Literature Review (SLR) method. The vast and growing expansion of the field of communication 5.0 through various digital platforms, such as social media, has made it difficult to communicate 5.0 in the current digital era, especially when connecting with Generation Z. The problem of communication in the current digital era is The current digital era, especially when interacting with Generation Z, is the rapid growth of the field of communication through various digital platforms, including social media, instant messaging, online content, other media, and so on. The characteristics of Generation Z, such as their tendency towards concise communication, strong visuals, and video, influence their communication style. Building a solid and productive partnership requires knowledge of the partnership and customization of your communication approach. In addition, it must be recognized that Generation Z is very tech-savvy, which can lead to privacy and security issues that need to be handled carefully if you want to establish effective communication with this generation.